Processo ensino-aprendizagem no ensino superior: teceduras à pedagogia emancipatória - Carvalho, Cláudia Regina Rodrigues de (2002)
The present work is fruit of an action-investigation with emphasis in the qualitative approach and in the perspective dialectics, having as study object the perceptions that the academic ones, in the seventh period of the course of Pedagogy of UNICRUZ, have concerning their existences in the process learning-teaching in the higher education and of the relationships that permeate it. For its development, the space/time of the classes was used supplied by the author close to the investigated group, in dynamics that prioritize reflection spaces, discussion, questions and problematizations, in an atmosphere of existence dialectics of the dialoguing. The authors' choice for the theoretical-practical sustentation of this investigation, felt for the prerogative of the line Freireana in the speakers' search that turned it alive in a process of - Reverse-flexing, rereading, reinvention, rediscovered. As prioritized indicators, in elapsing of all the investigation, they are present: perceptions concerning the process teaching-learning; theoreticalmethodological reasons that permeate the process teaching-learning in the course of Pedagogy of UNICRUZ and, needs and didactic-pedagogic possibilities for constitution of a emancipating pedagogy. Observed the indicators, the revealed information are worked in way cross they with the supporting referencial of the research. In that sense the work is divided in texts that try to demonstrate a (with) textuality dialectics that protects their peculiarities but that commit as parts of a totality, to cross the rising and the presentation of the perceptions of the academic ones around the central theme of the work, it is one of the largest challenges to him and for him tax, similar of drawing viable and maintainable alternatives for the existence of the emancipating pedagogy in the academical context. Among the possible lifted up alternatives, they stand out: the perception on the part of the teachers that the pedagogic practices in the course should be reconfigurated in a collective character of dialogue. The conflicts lived in the course should be better explained, so that with him all grow and learn; the meanings of learning and of teaching they should be revisited and (reverse) meanings in a dialectics theory-practice that notices them as complete for the unit and for the singularity; the course better should have the expressed criticalreflexive character in it PPP; effort and political-institutional compromising is the key word, once the institution is made by the subjects that shape it.